Implementasi PSAK No. 107 tentang Ijarah pada Pembiayaan Dana Talangan Haji di Bank Syariah - Muhammad Al Faruq; Nanik Wahyuni (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
This study aims to analyze the implementation of PSAK No. 107 concerning Financing of Hajj Bailout (DTH) Funds at Bank Tabungan Negara (BTN) Syariah Kantor Kas (KK) Sidoarjo. This type of research uses qualitative methods with a descriptive approach. The data source of this research consists of primary data and secondary data. This research data collection technique through observation, interviews and documentation. The observation of this research was carried out at Bank Tabungan Negara (BTN) Syariah Kantor Kas (KK) Sidoarjo which is located on Jl. Ahmad Yani, No. 3G, Sidokumpul, Pucang, Sidoarjo, East Java. Interviews were conducted with Account Officers, Tellers and Customer Service. Documentation was obtained from the customer's Hajj & Umrah Savings Book and the Financial Report of Bank Tabungan Negara (BTN) Syariah Kantor Kas (KK) Sidoarjo. The data analysis technique of this research was analyzed inductively. The results of this study indicate that the recording of Multiservice Financing transactions (Haji Bailout Funds) has been journalized based on the provisions issued by Pedoman Akuntansi Perbankan Syariah Indonesia (PAPSI) at years 2003 which are compiled based on PSAK No. 107. Bank Tabungan Negara (BTN) Syariah Kantor Kas (KK) Sidoarjo is not in accordance with PSAK No. 107 for not keeping records (journals) at the time the transaction occurred. Then when the customer makes an installment payment transaction for the Multiservice Financing (Hajj Bailout Fund) of Bank Tabungan Negara (BTN) Syariah Kantor Kas (KK) Sidoarjo does not recognize it as a deduction from the principal of the financing at the time the transaction occurs, this shows a discrepancy with the actual concept of recognition based on PSAK No. 107.